Deadbeat Predictive Algorithm-Based Back EMF Observer for Sensorless Control of PMSM Drives - An, Quntao; Zhao, Mengji; Ma, Teng; Wu, Youtong (IEEE transactions on industrial electronics (1982), 2025)
To improve the sensorless control performance of surface-mounted permanent magnet synchronous machine (SPMSM), this article proposes a back EMF observer based on deadbeat predictive algorithm. As for an observer, the regulatory mechanism is crucial. In the SMO, the observer achieves current state tracking through the hysteresis control, which leads to the chattering problem. To reduce the current tracking error, the deadbeat control is introduced as a regulator in the proposed new observer. This method estimates the control variables based on the sampled currents. The estimated currents can track the actual values in a single control cycle, which can greatly improve the dynamic response and accuracy of the observer. Furthermore, the characteristic of fast regulation makes it suitable for the low carrier ratio conditions. In this article, the stability and performance analysis are introduced in detail. The experimental results carried out on a 220 V, 1 kW PMSM demonstrate the effectiveness of the proposed method.